Improving Employee Performance: The Impact of Job Analysis, Work Discipline, and Workload: Meningkatkan Kinerja Karyawan: Dampak Analisis Pekerjaan, Disiplin Kerja, dan Beban Kerja - Jannah, Safira Nur; Sumartik (Indonesian Journal of Law and Economics Review, 2023)
This study aimed to investigate the impact of job analysis, work discipline, and workload on employee performance at PT.ALP Petro Industry in Pasuruan, using a quantitative approach. The population of the study consisted of 70 employees, and a sample size of 60 respondents was selected using random sampling. The data was analyzed using SPSS software. The findings of the study indicated that job analysis, work discipline, and workload had a significant effect on employee performance, both partially and simultaneously. These results suggest that improving job analysis, work discipline, and workload management can lead to better employee performance. The implications of this study are that companies should prioritize employee job analysis, work discipline, and workload management to improve overall performance and productivity. Highlights: The study highlights the significant impact of job analysis, work discipline, and workload on employee performance, both partially and simultaneously. The use of a quantitative approach and SPSS software for data analysis adds to the rigor of the study. The study's implication is that companies should prioritize improving job analysis, work discipline, and workload management to enhance employee performance and productivity.